Late Transition Metal Doped MXenes Showing Superb Bifunctional Electrocatalytic Activities for Water Splitting via Distinctive Mechanistic Pathways. Issue 48 (7th November 2021) - Anand, Rohit; Nissimagoudar, Arun S.; Umer, Muhammad; Ha, Miran; Zafari, Mohammad; Umer, Sohaib; Lee, Geunsik; Kim, Kwang S.
Abstract: MXenes have been widely used as substrates of hybrid electrocatalysts for water splitting due to their stability and metallic properties. However, tuning MXenes towards superb hydrogen/oxygen evolution reaction (HER/OER) activity has remained elusive. Using first‐principles calculations along with machine learning (ML) based descriptors, it is shown that late transition metal doping is able to significantly promote HER/OER activities. Both single‐atom adsorption onto a stable hollow site above the outer oxygen layer single‐atom catalyst 1 (SAC1), and single‐atom replacement at a sub‐surface metal layer (SAC2) are considered. An adsorbate evolving mechanism (AEM) is preferred for SAC1, while the increased M‐O bond covalency for SAC2 makes lattice oxygen mechanism (LOM) favored. It is found that a single Ni or Co atom embedded into MXenes provides a suitable number of electrons for optimal AEM and raises the O 2p band towards activated LOM. The stability and superb bifunctional catalytic capability of MXene combinations (Ni‐doped Sc3 N2 O2 and Ni‐doped Nb3 C2 O2 ) towards both HER and OER are demonstrated. The electronic and geometric descriptors used in the ML analysis work universally for classification of high‐performing HER/OER catalysts. This work provides a rational strategy for promoting bifunctional electrocatalytic activities based on low‐cost MXenes metals. Abstract : First‐principles calculations along with machine learning‐based descriptors are used to systematically screen promising water splitting catalysts. It is found that a single Ni or Co atom embedded into MXenes via different mechanistic pathways is able to promote hydrogen/oxygen evolution reaction activities. Ni‐doped Sc3 N2 O2 shows stability and bifunctional catalytic capability that are much better than commercially used noble metal catalysts.